Semantic modifications of the proposals being in the modern Ukrainian language - Жовтобрюх, Валентина Федорівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article examines the semantic modification of existential sentences, due to the peculiarities of lexical meaning of verbs functioning in life indicator position. Identified body of verbal tokens used in the sentences with the semantics of being, and the conditions for their use as equivalents existential verbs. Defined semantic features of verbal tokens that cause the displacement of the center of the being communicative offers, resulting in a modified its semantics. Semantic modifications manifest themselves in enriching the typical existential semantics proposals towards the development of the value of characterization and expansion of its expressive possibilities.